The Importance of Salicylic Acid, Humic Acid and Fulvic Acid on Crop Production - Shahrajabian, Mohamad H.; Sun, Wenli (Letters in Drug Design & Discovery, 2024)
Biostimulants are one of the most important substancesfor improving productivity, growth and yield of plants as well as heavy metal detoxification, and stimulating natural toxins, controlling pests and diseases and boosting both water and nutrient efficiency. Google Scholar, Science Direct, CAB Direct, Springer Link, Scopus, Web of Science, Taylor and Francis, and Wiley Online Library have been checked. The search was done to all manuscript sections according to the terms
Keywords: plant growth promotion